A Biologically Annotated List of the Buprestidae of the Lower Rio Grande Valley, Texas. (2nd December 2014) - Vogt, George B.
Abstract : During the period between January 1, 1946 and October 6, 1947, the writer collected insects regularly on weekends over much of the area generally known as the Lower Rio Grande Valley, Texas. The Buprestidae are well represented in the resulting collection and a list of the 63 species taken are here given with biological notes.